Modified α, α′-trehalose and d-glucose: green monomers for the synthesis of vinyl copolymers. Issue 5 (23rd May 2018) - Papacchini, A.; Telaretti Leggieri, M. R.; Zucchini, L.; Ortenzi, M. A.; Ridi, F.; Giomi, D.; Salvini, A.
Abstract : Allyl saccharide/vinyl copolymers were synthesized using renewable feedstocks (α, α′-trehalose and d -glucose) to obtain 'green monomers'. Properly designed synthetic procedures were used to obtain copolymers with high purity and without protection/deprotection steps in agreement with the principles of green chemistry and industrial sustainability. The use of saccharide derivatives as monomers allowed products to be obtained that showed high affinity and compatibility for the cellulosic substrates, like paper or wood, and that were suitable for applications like adhesion or consolidation in the field of cultural heritage. All reaction products were characterized by FT-IR and NMR spectroscopies and SEC analyses, while thermal properties were evaluated by DSC analyses.